The effect of dilution on the in vitro erosive potential of a range of dilutable fruit drinks - MARGARET L. HUNTER, RAJIV PATEL, THERESA LOYN, MARIA Z. MORGAN, RUTH FAIRCHILD, & JEREMY S. REES (IAPD and Blackwell, 2008)
The most recent UK Children’s Dental Health Survey found that 53% of 5-year-olds and approximately one-third of 12- and 15-yearolds had one or more teeth that had been affected by non-carious tooth surface loss.